In situ Orchid Seedling-Trap Experiment Shows Few Keystone and Many Randomly Associated Mycorrhizal Fungal Species During Early Plant Colonization - Cevallos, Stefania; Declerck, Stéphane; Suárez, Juan Pablo (Frontiers in Plant Science, 2018)
Orchids are known for their vast diversity and dependency on mycorrhizal fungi. Under in situ conditions, the biotic and abiotic factors determining the composition and distribution of orchid mycorrhizal fungi (OMF) communities remain largely unexplored. Therefore in situ experiments are needed to better understand the interactions between orchids and fungi. A seedling-trap experiment was conducted in the Reserva Biológica San Francisco, a well-known biodiversity hotspot located in the Andes of southern Ecuador. The objective was to investigate the effect of orchid species, site, elevation or temporal variation on the assembly and structure of OMF associated with Cyrtochilum retusum and Epidendrum macrum. The OMF community composition was determined using the Illumina MiSeq sequencing of the internal transcribed spacer 2 (ITS2) region. The results exhibited 83 OMF operational taxonomic units belonging to Tulasnellaceae, Ceratobasidiaceae, Serendipitaceae and Atractiellales. It was observed that the composition of the OMF communities was different among orchid species and temporal variation but was not different among sites. The results further support that orchids have a core of keystone OMF that are ubiquitously distributed and stable across temporal change, whereas the majority of these fungi are randomly associated with the plants.